Kegiatan Halaqoh dalam Pengembangan Sumber Daya Manusia di Lembaga Pendidikan Islam - Syafitri, Ayu; Jamilus, Jamilus (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2024)
Development of human resources is one of the key factors in achieving sustainability and success in Islamic educational institutions. There are several ways to develop human resources in Islamic educational institutions: 1) Islamic training and workshops; 2) Professional Development Program; 3) Collaboration with Islamic Education Institutions; 4) Research and Development Activities; 5) Use of Technology in Learning and 6) Development of Islamic Leadership and Ethics. Of these several ways, halaqoh activities are one of the activities that are considered to play an important role in developing human resources in Islamic educational institutions. This article aims to explain halaqoh activities in Islamic educational institutions as activities in human resource development. The method used is a library research approach by reading literature and collecting research materials. The results obtained are that halaqoh activities can provide many benefits to teachers, such as being able to help improve teacher professionalism, provide experience, add insight, knowledge and skills in designing learning methods, improve the quality and quantity of worship and teacher recitation of the Qur'an and improve the ability spiritual teacher. Keywords: Development, HR, Halaqoh Activities